The development of amivantamab for the treatment of non-small cell lung cancer - Danielle Brazel; Misako Nagasaka (Respiratory Research, 2023)
Abstract Non-small cell lung cancer (NSCLC) patients with sensitizing oncogenic driver mutations benefit from targeted therapies. Tyrosine kinase inhibitors are highly effective against classic sensitizing epidermal growth factor receptor (EGFR) mutations, such as exon 19 deletions and exon 21 L858R point mutations. Conversely, EGFR exon 20 insertions (exon20ins) are resistant to the traditional EGFR tyrosine kinase inhibitors (TKIs). In May 2021, the US Federal Drug Administration (FDA) provided accelerated approval to amivantamab (Rybrevant) in adults with locally advanced or metastatic NSCLC with EGFR exon20ins after treatment with platinum-based chemotherapy. Amivantamab was the first EGFR/MET bispecific antibody to be approved specifically for EGFR exon20ins where there was an unmet need. Furthermore, amivantamab is being evaluated in additional settings such as post osimertinib in sensitizing EGFR mutations as well as in MET altered NSCLC. Here we discuss amivantamab in regard to its mechanism of action, preclinical and clinical data, and clinical impact for patients with EGFR exon20ins NSCLC and beyond.